Advance system and model to predict malicious files prorogation inside computer network. Issue 1 (1st January 2019) - Ahmad, Ashraf; Abu Hour, Yousef S.; DarAssi, Mahmoud H.
Abstract : A new model for malicious file propagation and transmission in a computer network is formulated. This model introduced a cure rate ξ ( E ‐cure rate) which is calculated after the regular running of anti‐virus in the systems of the computer network. This will result in monitoring the anti‐virus efficiency in fighting not only a local malicious file but also the global spreading of such a file. The file has to go through different scenarios including many other states. Therefore, a vertical transmission concept is introduced in the proposed model. The threshold conditions for the stability of the proposed model are determined. Numerous methods are used to prove that the viral equilibrium points of our model are globally and locally stable. The behaviour of the compartment nodes in the computer network has been analysed. In addition, the optimal control theory is used to study immunisation strategies against Malware in order to control the economic losses of security investments and keep infection loss at the lowest possible level. The existence and uniqueness of results related to the system are confirmed. Finally, the simulation shows that the spread of malware can be effectively controlled by choosing the appropriate control strategy of specific parameters.